A Contemporary Systematic Approach to Assessing the Patient with Heart Failure with Reduced Ejection Fraction: Multimodal Noninvasive and Invasive Evaluation. (11th September 2019) - Wan, Siu-Hin; McKie, Paul M.; Bois, John P.
Abstract : Heart failure with reduced ejection fraction (HFrEF) is a progressive clinical syndrome commonly associated with left ventricle dilatation and characterized by reduced cardiac output, secondary pulmonary and systemic venous congestion, and inadequate peripheral oxygen delivery. It is common yet complex and requires synthesis of evidence-based guidelines along with strong clinical acumen. The following is a review of an illustrative case that highlights the important clinical considerations in diagnosis, assessment, and management of HFrEF commonly encountered in practice. Explanations provided highlight of the relevant pathophysiology of HFrEF as well as detailed explanations of interpretation of examinations and both noninvasive and invasive assessment in heart failure. The example provided would hopefully serve as a potential point of reference for trainees as well as healthcare practitioners for patients with HFrEF.